2021
DOI: 10.3390/microorganisms9102137
|View full text |Cite
|
Sign up to set email alerts
|

The Predatory Myxobacterium Citreicoccus inhibens gen. nov. sp. nov. Showed Antifungal Activity and Bacteriolytic Property against Phytopathogens

Abstract: The application and promotion of biological control agents are limited because of poor efficacy and unstable performance in the field. Screening microorganisms with high antagonistic activity, effective adaptability, and high field-survival should be prospected. Myxobacteria are soil predatory bacteria with wide adaptability, which are considered as good antagonists. Here, we report a myxobacterium strain M34 isolated from subtropical forest soil in South China using the Escherichia coli baiting method. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Interestingly, we found that Citreicoccus inhibens gen. nov. sp. nov. M34 suppressed or predated a variety of phytopathogen mainly by secreting secondary metabolisms (Zhou et al, 2021). Generally speaking, we speculate that this may be related to the differences between different species in the coevolution process of myxobacteria, plants, and microorganisms.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, we found that Citreicoccus inhibens gen. nov. sp. nov. M34 suppressed or predated a variety of phytopathogen mainly by secreting secondary metabolisms (Zhou et al, 2021). Generally speaking, we speculate that this may be related to the differences between different species in the coevolution process of myxobacteria, plants, and microorganisms.…”
Section: Discussionmentioning
confidence: 80%
“…The predatory products of myxobacteria, including secondary metabolites and hydrases showing promising antimicrobial activities, have been reported ( Sasse et al, 2003 ; Zhou et al, 2021 ; Zhang et al, 2023b ). While most studies have focused on antibiotic production by myxobacteria, there are only a few reports about their enzymatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the prey structure, macromolecule components found in the cell wall, cytomembrane, and nucleus are targets of lytic weapons from myxobacteria. In fact, myxobacteria genomes encode numerous peptidases, glycoside hydrolases, polysaccharide lyases, and carbohydrate esterases ( Schneiker et al, 2007 ; Zhou et al, 2021 ; Wang et al, 2022 ), which likely target the prey structure in the process of predation. For example, glycoside hydrolases from myxobacteria targeting peptidoglycan in Gram-positive bacteria or β-1,6-glucans in fungi cell walls have been characterized and shown to contribute to prey biomass disruption of predation ( Li et al, 2019 ; Arend et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myxobacteria are excellent resources for discovery of therapeutics and are suggested to be keystone taxa influencing polymicrobial community structure in soil (1,2, 66–68). Recent discoveries of novel Corallococcus, Myxococcus , and Pyxidicoccus species as well as species from lesser-studied genera indicate an abundance of uncharacterized myxobacteria (10–12, 14–17, 69–79). Our investigation of rhizospheric soil samples provided 20 environmental myxobacteria including 9 proposed novel species.…”
Section: Discussionmentioning
confidence: 99%